Deep eutectic solvents: biorenewable reaction media for Au(i)-catalysed cycloisomerisations and one-pot tandem cycloisomerisation/Diels–Alder reactions1. Issue 7 (6th July 2015) - Vidal, C.; Merz, L.; García-Álvarez, J.
<x xml:space="preserve">Abstract</x> Cycloisomerisation reactions of (Z)-enynols can be conveniently performed in the eutectic mixture 1ChCl/2Gly under standard bench experimental conditions by using the novel Au(i) complex 3 as catalyst. Furthermore, one-pot tandem cyclosiomerization/Diels–Alder reactions are reported in this eutectic mixture.